Consumer Protection for Honda Vehicle Users with Frame eSAF Damage Based on the Principles of Consumer Safety and Security - Muhammad Alfito Prawidiya Utama; Muthia Sakti (Dinasti Research, 2024)
Two-wheeled vehicles are one of the primary modes of transportation for the majority of the population today. Honda, a leading manufacturer of two-wheeled vehicles, dominates the market in Indonesia by continually introducing innovations that meet consumer needs. Honda's latest innovation is the Enhanced Smart Architecture Frame (e-SAF). However, in some cases, this frame has experienced damage due to corrosion, which can be detrimental and even dangerous to consumers. This research used a normative legal research method, utilizing a literature review of positive law, data, and other legal materials, supplemented by interviews. The objective of this study is to analyze the aspects of legal protection for consumers using Honda vehicles with eSAF frame damage based on the principles of consumer safety and security. The research results indicated that in this case, Honda did not apply the principles of consumer safety and security, which should be an obligation for businesses to ensure the safety and security of their consumers. Legal protection for eSAF frame users is also assured by Law No. 8 of 1999 regarding Consumer Protection, which offers a robust basis for safeguarding consumer rights, especially their right to safety and security.